Pengaruh Pemberian Pupuk Organik Cair Daun Lamtoro dan NASA terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Glen Kristian Tuerah; I Gusti Alit Gunadi; I Nyoman Gede Astawa (Fakultas Pertanian, Universitas Udayana, 2023)
Pakcoy (Brassica rapa L) is a mustard vegetable plant that has a short harvest time, wide adaptability and long-lasting product results because it can be stored for up to 10 days after harvest at a temperature of 0 - 5 oC with 95 % humidity. Pakcoy plants when viewed from the economic and business aspects are feasible to be developed or cultivated to meet consumer demand which is getting higher and higher and there are high market opportunities. This study aims to determine the effect of lamtoro leaf liquid organik fertilizer and NASA on the growth and yield of pakcoy plants (Brassica rapa L.). This study used a randomized block design with 3 treatments, namely P0 (control), P1 (POC lamtoro leaves) and P2 (POC NASA) with 9 replications each. This research was conducted in the greenhouse of the Experimental Garden of the Faculty of Agriculture and the Laboratory of Agronomy and Horticulture, Udayana University from February to May 2023. The results showed that the application of lamtoro leaf liquid organik fertilizer had a significant effect on leaf area, plant dry weight and leaf chlorophyll content of pakcoy plants. (Brassica rapa L.), while the application of NASA liquid organik fertilizer had a significant effect on almost all observed variables, except for the net assimilation rate of pakcoy plants (Brassica rapa L.).